Light at the end of the tunnel: Clinical features and therapeutic prospects of KRAS mutant subtypes in non-small-cell lung cancer - Gao, Liyuan; Shen, Weizhang (Frontiers in Genetics, 2022)
Lung cancer is one of the most common causes of death in tumor patients, in which non-small cell lung cancer (NSCLC) accounts for about 85% of all lung cancer patients. KRAS (Kirsten Rat sarcoma Viral oncogene), one of the 3 subtypes in the RAS family, is the most common oncogene in human cancers and encodes key signaling proteins in tumors. Oncogenic KRAS mutations are considered to be the initiating factor in 30% of NSCLC cases, accounting for the largest proportion of NSCLC cases associated with driver mutations. For a long time, it has been difficult to effectively inhibit the related functions of KRAS with traditional small-molecule inhibitors, so KRAS protein has been called “undruggable target”. However, in recent years, the discovery of a common mutation in KRAS gene, G12C(glycine 12 mutated to cysteine), has led to the design and synthesis of covalent inhibitors that offer new hope for effective targeting of "un druggable target" KRAS. In this review, we will summarize the structure, function and signal transduction pathway of KRAS, and emphasize the treatment status and potential treatment prospects of KRAS mutation subtypes (especially G12C, G12V and G12D) in NSCLC, providing reference for the treatment selection of KRAS mutation subtypes in NSCLC.